2014
DOI: 10.1016/j.jaci.2014.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced innate type 2 immune response in peripheral blood from patients with asthma

Abstract: Background In mice, group 2 innate lymphoid cells (ILC2s) likely mediate helminth immunity, inflammation and tissue repair and remodeling. However, the involvement of ILC2s in human diseases, such as asthma, is not well understood. Objective The goals of this study were to investigate whether peripheral blood specimens can be used to monitor innate type 2 immunity in human subjects and to examine whether ILC2s are involved in human asthma. Methods Peripheral blood mononuclear cells (PBMCs) from subjects wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
328
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(348 citation statements)
references
References 43 publications
18
328
0
2
Order By: Relevance
“…Particularly, since recent studies in human provided evidence that ILC2s may be responsible for steroid-resistant asthma. ILC2 numbers are increased in sputum and peripheral blood of patients with severe asthma compared to mild asthmatics or healthy controls [45,46]. Importantly, evidence was found for a role of uncontrolled localized production of IL-5 and IL-13 by a steroid-insensitive population of ILC2s, in agreement with in vitro studies showing that ILC2s are steroidinsensitive in the presence of TSLP [46,47].…”
Section: Discussionsupporting
confidence: 79%
“…Particularly, since recent studies in human provided evidence that ILC2s may be responsible for steroid-resistant asthma. ILC2 numbers are increased in sputum and peripheral blood of patients with severe asthma compared to mild asthmatics or healthy controls [45,46]. Importantly, evidence was found for a role of uncontrolled localized production of IL-5 and IL-13 by a steroid-insensitive population of ILC2s, in agreement with in vitro studies showing that ILC2s are steroidinsensitive in the presence of TSLP [46,47].…”
Section: Discussionsupporting
confidence: 79%
“…Whilst the physiological role of ILC2 in human airway inflammation is not fully understood, ILC2 were shown to be elevated in nasal biopsies of chronic rhinosinusitis patients as compared to healthy controls (Mjosberg et al 2011) demonstrating an association of these cells with human disease. Moreover, a recent report has shown that the prevalence of ILC2 in the blood of allergic asthma patients was substantially higher than either allergic rhinitis patients or healthy controls (Bartemes et al 2014). These results are consistent with a role for ILC2 in the immunopathology of allergic asthma in humans.…”
Section: Role Of Ilc2 In the Pathogenesis Of Allergic Inflammationsupporting
confidence: 82%
“…45 Increased ILC2s are found in blood of asthma patients, and these cells produced more IL-5 and IL-13 in response to IL-25 or IL-33 compared to healthy controls or AR patients. 46 Whereas similar peripheral blood ILC2 proportions were found in asthma patients and controls in an earlier study, 47 the finding of increased ILC2 numbers in patients with asthma was confirmed by several subsequent reports. 42,48,49 Taken together, these studies suggest the involvement of ILC2s in specific subgroups of asthma ( Figure 1).…”
Section: Ilc3ssupporting
confidence: 58%